Absence of polyomavirus JC in glial brain tumors and glioma-derived cell lines - Wegner, Michael; et al. (Glia, 1998)
The human neurotropic papovavirus JC, a close relative of simian virus 40, has been associated with the formation of brain tumors in humans because of its ability to induce such tumors in other primates under experimental conditions. Here we have analyzed 30 brain tumors classified as either oligodendroglioma or astrocytoma and 22 cell lines derived from human gliomas for the presence of JC viral sequences using polymerase chain reaction with two different sets of primers. None of the tumors or cell lines contained JC viral sequences. Similarly, we failed to detect expression of JC T antigen in any of 26 human glioma lines analyzed in this study. We conclude that JC virus is not a major cause of human brain tumors.
UnivIS-Import:2015-03-05:Pub.1998.med.IB.LPCIPDBI.absenc
Keywords: Astrocytoma; Glioblastoma; JCV; Oligodendroglioma; PML